Helicid alleviates pain and sleep disturbances in a neuropathic pain‐like model in mice. (20th March 2017) - Zhang, Meng‐Qi; Wang, Tian‐Xiao; Li, Rui; Huang, Zhi‐Li; Han, Wu‐Jian; Dai, Xiao‐Chang; Wang, Yi‐Qun
Summary: Natural helicid (4‐formylphenyl‐O‐ β ‐d ‐allopyranoside), a main active constituent from seeds of the Chinese herb Helicia nilagirica, has been reported to exert a sedative, analgesic and hypnotic effect, and is used clinically to treat neurasthenic syndrome, vascular headaches and trigeminal neuralgia. In the current study, mechanical allodynia tests, electroencephalograms, electromyogram recordings and c‐Fos expression in neuropathic pain‐like model mice of partial sciatic nerve ligation were used to investigate the effect of helicid on neuropathic pain and co‐morbid insomnia. Our results showed that helicid at a dose of 100, 200 or 400 mg kg −1 could increase the mechanical threshold by 2.5‐, 2.8‐ and 3.1‐fold for 3 h after administration, respectively. Helicid at 200 and 400 mg kg −1 given at 07:00 hours increased the amount of non‐rapid eye movement sleep in a 3‐h period by 1.27‐ and 1.35‐fold in partial sciatic nerve ligated mice. However, helicid (400 mg kg −1 ) given at 21:00 hours did not change the sleep pattern in normal mice. Immunohistochemical study showed that helicid (400 mg kg −1 ) administration could reverse the increase of c‐Fos expression in the neurons of the rostral anterior cingulate cortex and tuberomammillary nucleus, and the decrease of c‐Fos expression in the ventrolateral preoptic area caused by partial sciatic nerve ligation. These results indicate that helicid is an effective agent for both neuropathic pain and sleep disturbances in partial sciatic nerve ligated mice.